“I Have No Name for That! Feeling is All in All...” - Sodeika, Tomas (Religija ir kultūra, 2012)
The article deals with the concept of feeling by Friedrich Schleiermacher. Aiming to reestablish the privileges of religion, violated by the secular culture of the Enlightenment, Schleiermacher tries to defend the rights of feeling debased by the modern rationalism. He denies that religion is a form of knowledge or morality. To Schleiermacher, religion cannot be based on morality nor on metaphysics or science. According to him, the essence of religion is neither thinking nor acting, but the feeling or, more specifically, feeling of absolute dependence. Such form of inner experience Schleiermacher identifies as immediate self-consciousness. Supposed that Schleiermacher’s texts can be treated as phenomenological descriptions in the Husserlian sense, the article deals with the ways of representating the ontological structure of the immediate self-consciousness in those texts.
Keywords: feeling; religion; Schleiermacher; self-consciousness; phenomenology